Impact of Economic Development Activities for Livelihood Security and Social Inclusion of Dalits: A Lesson from Ilisscon Project - Adhikari, Sharad; Giri, Chuda Raj; Lama, Taralal (Economic Journal of Nepal, 2014)
A study was carried out to measure the contribution of socioeconomic development activities for livelihood security and social inclusion of Dalits in ILISSCON project of LI-BIRD. Sample survey was used in the study for collecting the qualitative and quantitative data. Project results shows that average annual household income of the Dalits has been increased by Rs. 56,861.27 (increment 48.19%) from baseline and similar result was also observed in Janjati (Rs.57581.54) and Brahmin (Rs.66243.75) groups. Such increment on income of the beneficiaries was result of positive growth on the production and diversification of the livelihood sources. Majority of Dalits households (46.57%) have food sufficiency for more than 6 months as compare to baseline (10.47%). Participation of the Dalits and disadvantaged groupshas been remarkably increased in development activities, which shows important indication of the empowerment and inclusion of excluded groups. As a result, they are able to make meaningful exercise of their right with different service providers. Therefore, economic development activities have made significant contribution for social and economic empowerment, livelihood security and social inclusion.